Investigating the reasons why Singapore national water polo players continue play in their sport - Soo, Natalie Yu Xuan (Nanyang Technological University, 2024)
This paper investigates the reasons why Singapore’s national water polo athletes have decided to continue playing their sport. There are no proposed hypotheses for this study due to its inductive nature. Adopting a mixed-methods approach, survey data using the Sport Commitment Questionnaire-2 (SCQ-2) and four focus group discussions were conducted. The Framework Analysis method was used to organize and analyse interview data, and the Mann-Whitney U-test was used to analyse survey data. Quantitative results show significant differences between groups in multiple factors such as sport enjoyment, social constraints and desire to excel. Qualitative data showed that athletes found sport enjoyment, coach’s support, workplace, family and school support to be important factors in their continuity. Using the Lifespan Model, coach’s support played an important role in providing athletes with perceived good support during their developmental and mastery athletic stages. Other modes of support aided in better management between training and school/ work, allowing better coping abilities between responsibilities from different life domains. Future studies can focus on motives and drives of continuation, as well as expanding the scope of study to other sport disciplines.